Strategic impacts of information technology investments on banking industry performance: evidence from a cross-country analysis for Brazil, United States, Argentina, Uruguay and Chile - Lunardi, Guilherme Lerch (2015)
Submitted by Raquel Vergara Gondran (raquelvergara38@yahoo.com.br) on 2015-09-01T16:14:48Z No. of bitstreams: 1 000395005.pdf: 68690 bytes, checksum: a636eb2f4681ecb3119759fd9f8d3769 (MD5)